The Water Industry Privatization in China - Sun, Hua (2009)
In the decades of 1990s and 2000s, there is a very obvious feature in China that is a shift in state controlled politico-economic management paradigm given way to a progressively liberalist and free market reform creed. Consequently, China inclined towards a re-institutionalization of her economic orientations along the notions of privatization and de-regulation. During the process, a variety of measures have being undertaken to refresh the operations of government along market lines, which is perceived to bring more growth and development. The measures range from restructuring the state institutions for good governance and privatization of state-owned enterprises to opening up the markets to international and domestic investors. Among those state-owned company a lot of them are public services or utilities (such as water supply, telephone, etc. ) concerned companies, these companies acquires greater significance for consumers and citizens in the context of privatization since these sectors have traditionally been owned and managed by the state. Their privatization, de-regulation and de-monopolization mean breaking the government monopolies over them by involving the private and foreign sector in their delivery. Under privatization, the control rights of water works are transferred to private interests so that public subsidies decline. This benefit for tax-payers comes at the cost of price increases for consumers. In China, tight budget constraints imply that privatization may be optimal for low profitability segments. However, immense criticism against privatization has also come from a variety of issues related to these public utilities. The critics of the privatization of these sectors maintain that where liberalization and privatization has created new opportunities for foreign and domestic investors, it has inevitably resulted in some constraints as well. These constraints are centred around the concerns of the consumers, which include, cost, service, issues regarding their regulation, particularly in case of private monopolies, pricing, tariff, shedding of workforce, equity and accessibility. Most important issue among them is perhaps the problems related to equity and access to basic, universal and essential goods and services price for the poor, disadvantaged and marginalized consumers. This paper analyzes governments’ tradeoff between fiscal benefits and consumer surplus in privatization reforms of noncompetitive water industries in China. For highly profitable public utilities such as water industry, the combination of allocative inefficiency and critical budgetary conditions may favor public ownership. Once a market segment gives room for more than one firm, governments should to regulate the industry. In China, the absence of a credible regulatory agency and policy caused the price of water raised up at very high percentage; it is becoming a more and more outstanding problem.